Non-governmental organisations and poverty reduction in the north west and east regions of Cameroon - Nsah, Edwin Saka (Department of Sociology, 2022)
Literature on NGOs and poverty reduction shows inconsistencies in NGOs adding value to poverty reduction. E.g. some researchers have criticized developmental NGOs for not supporting the needy. Contrarily, some have argued that NGOs provide for the underprivileged. NGOs in Cameroon do not pose issues different from the above. What worries Cameroonians most is the fact that a high number of developmental NGOs are created in the same areas. On the other hand, poverty is getting widespread in the same areas serviced by these NGOs. This study analyses why NGOs participate in poverty reduction programmes given that these programmes do not reduce poverty. To achieve the aim of the study, six objectives were established: (1) Establishing the reasons for continued increase in poverty in the selected regions. (2) Exploring how NGO staffs and their beneficiaries perceive poverty. (3) Understanding the nature of participation (4) Understanding reasons donors give funding to NGOs. (5) Investigating the challenges NGOs encounter. (6) Finally formulating suggestions that may lead to better integration of programmes designed. The study was conducted in Cameroon and a qualitative research design was used. Access into the field was established through informal telephone calls, emails, and covering letters to General Managers seeking their consent to use their organisations for this research. Purposive and Snowball sampling was used to select the study participants based on their links with the study NGOs. The study adopted the triangulation approach. The study found that selected NGOs programmes continue to fail because there were extraneous variables which account for ineffectiveness in NGOs poverty reduction programmes. For example, poverty reduction in any nation is the duty of every government and its citizens to fight against poverty and NGOs only assist as support mechanisms towards the realization of government obligations to its citizens, here the government and it citizen were not doing enough to fight poverty. Attributing poverty reduction only to NGOs is demanding too much from them. In conclusion, NGOs are purporting to have made real achievements in poverty alleviation but in reality their programmes are benefitting only a few from the grave effects of poverty because they are more involved with charity work. The study suggests that, dialogue with all NGOs stakeholders will reduce possible contradiction and will improve coordination and collaboration between the actors.